Passion and Virtue in Cartesian Moral - Lázaro, Raquel (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
Descartes plays a central role in the origin of Modern Philosophy. His method and the cogito open a new way of thinking. Sometimes, Cartesian moral is considered a minor contribution in his system; but what does Descartes think about it? He understands that philosophy is intimately related to the need of finding a practical guide for action. Virtue and passions are indeed present in the Cartesian moral, but they are given a new sense. In Descartes the virtuous person is the generous man, not the prudent one. Unlike stoics, he grants a fundamental role to passions in the order of action. This paper aims to show how these concepts are related to those of «good will» and «sovereign good» in the Cartesian moral, since we understand that the practical part of his philosophy was a principal question in Descartes, as well as, in the rest of the modern philosophers.